2005
DOI: 10.1136/bmj.330.7488.396
|View full text |Cite|
|
Sign up to set email alerts
|

Association between suicide attempts and selective serotonin reuptake inhibitors: systematic review of randomised controlled trials

Abstract: Objective To establish whether an association exists between use of selective serotonin reuptake inhibitors (SSRIs) and suicide attempts. Design Systematic review of randomised controlled trials. Data sources Medline and the Cochrane Collaboration's register of controlled trials (November 2004) for trials produced by the Cochrane depression, anxiety, and neurosis group. Selection of studies Studies had to be randomised controlled trials comparing an SSRI with either placebo or an active non-SSRI control. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
197
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(218 citation statements)
references
References 13 publications
9
197
1
11
Order By: Relevance
“…Accordingly, the present study is restricted to studies with information on suicides and suicide attempts. Similar to our experience, Fergusson et al [23], in their meta-analysis of suicide attempts under SSRIs, found that less than half of all trials reported on suicide attempts. They also concluded that ‘a substantial proportion of suicide attempts have gone unreported'.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Accordingly, the present study is restricted to studies with information on suicides and suicide attempts. Similar to our experience, Fergusson et al [23], in their meta-analysis of suicide attempts under SSRIs, found that less than half of all trials reported on suicide attempts. They also concluded that ‘a substantial proportion of suicide attempts have gone unreported'.…”
Section: Discussionsupporting
confidence: 69%
“…Our result of a lack of proof regarding a protective effect of antidepressants on suicide or suicide attempts is in line with meta-analyses primarily focusing on acute treatment studies: none of the 8 meta-analyses of antidepressant RCTs known to the authors resulted in statistically significant superiority compared to placebo [18,19,20,21,22,23,65,66]. The suicide event rate is low, precluding definite conclusions, but if there is any signal from these meta-analyses, it is that there may be a marginal suicide risk increase with antidepressants.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…11 Meanwhile, the OHIE showed that the acquisition of Medicaid significantly reduces depression rates (Baicker et al, 2013), raising the possibility that coverage might also reduce suicide rates. While some trials of specific cognitive interventions have been shown to reduce recurrent suicide attempts (Brown et al, 2005), the most common medical intervention for depression (antidepressant use) has not been shown to reduce suicides in randomized trials (Fergusson et al, 2005), and the overall evidence base is mixed as to whether medical care reduces the risk of self-harm (Hawton et al, 2000). Thus, it is reasonable to assume that any mortality effects mediated by insurance coverage should be larger for healthcareamenable causes than for these other causes of death.…”
Section: Iiic Analyses Of All-cause Mortalitymentioning
confidence: 99%
“…Independent review of adverse events from data from 24 placebo-controlled trials of AD use in children and adolescents found that suicidality significantly increased with SSRI treatment compared to placebo, leading the FDA to issue a “black box” warning (see Brent, 2004; Goodman et al , 2007; Newman, 2004). Additional studies have likewise found evidence of increased suicidality with use of SSRIs in juveniles, suggesting that there may be an unfavorable risk to benefit ratio for SSRIs (with fluoxetine as a possible exception) (Bailly, 2008; Barbui et al , 2009; Bridge et al , 2007; Cipriani et al , 2005; Doggrell, 2005; Fergusson et al , 2005; Goodman et al , 2007; Hammad et al , 2006; Laughren, 2006; Mosholder and Willy, 2006; Olfson and Marcus, 2008; Olfson et al , 2006; Richmond and Rosen, 2005; Ryan, 2005; Scahill et al , 2005; Tiihonen et al , 2006; Vitiello and Swedo, 2004; Whittington et al , 2004; Wohlfarth et al , 2006). Many of these and other studies have pointed out difficulties in interpretation of the data and have stated that there is considerable risk for suicidality if pediatric patients are not adequately treated (e.g., Bridge et al , 2007; Mann et al , 2006).…”
Section: Discussionmentioning
confidence: 99%